Orchid bee fauna responds to habitat complexity on a savanna area (Cerrado) in Brazil - Antonini, Yasmine; Silveira, Rodrigo Assunção; Oliveira, Marcio Luiz de; Martins, Cristiane; Oliveira, Reisla (Sociobiology, 2016)
Here we investigated responses of orchid bee assemblages to habitat complexity, with the aim of assessing complexity as a useful surrogate for species diversity of this group. For the purposes of our study, we defined habitat complexity as the heterogeneity in the arrangement in physical structure of habitat (vegetation), although there is a large range of operational definitions in the literature. We test the following hypotheses: (i) There is a greater species richness and abundance of orchid bee in sites with high habitat complexity than lower habitat complexity; (ii) High habitat complexity sites have a different species composition of orchid bee than lower habitat complexity sites. In fact, orchid bee species richness was higher in high complexity areas while community composition was not affected by habitat complexity, due to the effect of dominant species. Habitat complexity, measured as a function of differences in multiple strata in forests, may be of great worth as a surrogate for the diversity of a range of arthropod groups including orchid bees.